Cisco router configuration - Leinwand, Allan (Cisco Press design and implementation series., 1998)
Cisco Router Configuration takes an example-oriented and chronological approach to helping you implement and administer your internetworking devices. Starting with the configuration of devices "out of the box," this book moves to configuring the Cisco IOS for the three most popular networking protocols used today: Transmission Control Protocol/Internet Protocol (TCP/IP), AppleTalk, and Novell InterPacket eXchange (IPX). You also will learn basic administrative and management configuration, including access control with TACACS+ and RADIUS, network management with SNMP, logging of messages, and time control with NTP.